2016
DOI: 10.1158/0008-5472.can-16-0396
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Landscape of Acquired Resistance to Targeted Therapy Combinations in BRAF-Mutant Colorectal Cancer

Abstract: Summary Although recent clinical trials of BRAF inhibitor combinations have demonstrated improved efficacy in BRAF mutant colorectal cancer, emergence of acquired resistance limits clinical benefit. Here, we undertook a comprehensive effort to define mechanisms underlying drug resistance with the goal of guiding development of therapeutic strategies to overcome this limitation. We generated a broad panel of BRAF mutant resistant cell line models across seven different clinically-relevant drug combinations. Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 49 publications
(75 reference statements)
5
73
0
Order By: Relevance
“…These results are aligned with previous reports that CRC cell lines may contain pre-existing but low levels of RAS mutations, but they can also acquire mutations de novo 20. This would apply to the acquisition of mutations in the EGFR ECD during anti-EGFR therapy as there have been no reports of these mutations pre-existing in cell lines or patients before anti-EGFR therapy1011122136.…”
Section: Discussionsupporting
confidence: 90%
“…These results are aligned with previous reports that CRC cell lines may contain pre-existing but low levels of RAS mutations, but they can also acquire mutations de novo 20. This would apply to the acquisition of mutations in the EGFR ECD during anti-EGFR therapy as there have been no reports of these mutations pre-existing in cell lines or patients before anti-EGFR therapy1011122136.…”
Section: Discussionsupporting
confidence: 90%
“…The detection of acquired mutations or amplification of KRAS in disease progression tumor biopsies in 4 of 6 responders is an important finding, and is consistent with drug resistance being driven through MAPK pathway reactivation in BRAF mutant CRC (1,7,9). Preliminary data from the SWOG S1406 randomized phase 2 trial of irinotecan and cetuximab, with or without vemurafenib, in BRAF mutant metastatic CRC reported an improvement in progression-free survival with the triplet combination, with toxicity rates similar to doublet regimens of irinotecan and cetuximab.…”
supporting
confidence: 56%
“…However, the occurrence of therapeutic resistance continues to be a significant cause of the failure of current combination therapy. It has been demonstrated that the acquisition of resistance can occur following combination treatment and that the use of a third agent can address the emergence of resistance by inhibiting a factor involved in the resistance [10,11,189]. This implies that the multiple targeting of resistance-mediating factors is better than the current approach to increase the cellular response to cancer therapy and that the development of new combination strategies is still required to improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%